If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -1(p + 30) = 6(p + -5) + 4p Reorder the terms: p + -1(30 + p) = 6(p + -5) + 4p p + (30 * -1 + p * -1) = 6(p + -5) + 4p p + (-30 + -1p) = 6(p + -5) + 4p Reorder the terms: -30 + p + -1p = 6(p + -5) + 4p Combine like terms: p + -1p = 0 -30 + 0 = 6(p + -5) + 4p -30 = 6(p + -5) + 4p Reorder the terms: -30 = 6(-5 + p) + 4p -30 = (-5 * 6 + p * 6) + 4p -30 = (-30 + 6p) + 4p Combine like terms: 6p + 4p = 10p -30 = -30 + 10p Add '30' to each side of the equation. -30 + 30 = -30 + 30 + 10p Combine like terms: -30 + 30 = 0 0 = -30 + 30 + 10p Combine like terms: -30 + 30 = 0 0 = 0 + 10p 0 = 10p Solving 0 = 10p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-10p' to each side of the equation. 0 + -10p = 10p + -10p Remove the zero: -10p = 10p + -10p Combine like terms: 10p + -10p = 0 -10p = 0 Divide each side by '-10'. p = 0 Simplifying p = 0
| y=-[2x+3] | | 4y=300-x | | 7c+14=16 | | 12n=1722n | | f(x)=x-2 | | 4x(3x+4)=3 | | 1/2+21/2 | | 23+8g=-4.2 | | 6(3n+2)=9(7n+4)+2 | | 2x+12=14-7x+14 | | 6x^2+21x=-15 | | x+(x+11)+(3x-16)=730 | | -6f+10=-14 | | b=8-6/4 | | 6s^2-52+1=0 | | (x^4+x^2-6)/(x^2+3) | | d=a/25m^2 | | -3(-x^2+5)=39 | | 68/4 | | T=L(5+RS)forS | | 56-x^2=20 | | 5-6d+2d=-17 | | 6x=71/2 | | 4x=-31 | | 7-2(3x+5)=3 | | A=25m^2 | | T=L(5+RS) | | 1+3y=6y-1/5 | | 4x(x-2)(2x+3)=0 | | (18-2x)(15-2x)(42-x)=6160 | | 2x^2-1=49 | | 2(x-3)(x+8)=0 |